2016
DOI: 10.1182/blood-2015-04-640920
|View full text |Cite
|
Sign up to set email alerts
|

Pevonedistat, a NEDD8-activating enzyme inhibitor, is active in mantle cell lymphoma and enhances rituximab activity in vivo

Abstract: Key Points• Pevonedistat (MLN4924), a NEDD8-activating enzyme inhibitor, is active in MCL preclinical models and potentiates rituximab activity.• Our findings support further investigation of pevonedistat with or without rituximab in the treatment of MCL.Mantle cell lymphoma (MCL) is characterized by an aggressive clinical course and inevitable development of refractory disease, stressing the need to develop alternative therapeutic strategies. To this end, we evaluated pevonedistat (MLN4924), a novel potent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Significant survival benefit was noted in mouse models with pevonedistat alone or in combination with cytarabine or ibrutinib when compared with cytarabine or ibrutinib monotherapy. In contrast to what we observed in mantle cell lymphoma (MCL) pre‐clinical models [23], pevonedistat did not consistently improve anti‐tumor activity of rituximab in DLBCL.…”
Section: Discussioncontrasting
confidence: 99%
“…Significant survival benefit was noted in mouse models with pevonedistat alone or in combination with cytarabine or ibrutinib when compared with cytarabine or ibrutinib monotherapy. In contrast to what we observed in mantle cell lymphoma (MCL) pre‐clinical models [23], pevonedistat did not consistently improve anti‐tumor activity of rituximab in DLBCL.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, we found that NF‐κB inhibition occurred earlier than PI3K/mTOR signaling suppression upon NAE inhibition; that is, the transcription of NF‐κB‐targeted genes was downregulated after 4 hours of treatment with TAS4464 in cell lines KMS‐11, KMS‐12‐BM, KMS‐26 and MM.1S (Figure C). Further studies are needed to examine the extent to which the inhibition of each pathway is involved in the anti–MM activities of these compounds; however, MLN4924 rapidly increased the levels of p‐IκBα and p‐p100 in MM cells (Figure ) and is reported to inhibit the NF‐κB pathway in other hematological malignancies such as diffuse large B‐cell lymphoma and B‐cell chronic lymphocytic leukemia …”
Section: Discussionmentioning
confidence: 99%
“…MLN4924 can inhibit DLBCL cell line growth including ABC and GCB subtypes and can inhibit ABC-DLBCL tumors in xenograft mice models [157]. Another study found that MLN4924 is active in MCL and improves rituximab activity in vivo patient care [158]. In a phase I study, it was shown that 71% of 42 patients with relapsed and/or refractory lymphoma who had ≥1 post-baseline disease assessment achieved stable disease.…”
Section: Therapeutic Approachesmentioning
confidence: 99%